Decompressive laparotomy for abdominal compartment syndrome. Issue 6 (18th February 2016) - De Waele, J. J.; Kimball, E.; Malbrain, M.; Nesbitt, I.; Cohen, J.; Kaloiani, V.; Ivatury, R.; Mone, M.; Debergh, D.; Björck, M.
Abstract : Background: The effect of decompressive laparotomy on outcomes in patients with abdominal compartment syndrome has been poorly investigated. The aim of this prospective cohort study was to describe the effect of decompressive laparotomy for abdominal compartment syndrome on organ function and outcomes. Methods: This was a prospective cohort study in adult patients who underwent decompressive laparotomy for abdominal compartment syndrome. The primary endpoints were 28‐day and 1‐year all‐cause mortality. Changes in intra‐abdominal pressure (IAP) and organ function, and laparotomy‐related morbidity were secondary endpoints. Results: Thirty‐three patients were included in the study (20 men). Twenty‐seven patients were surgical admissions treated for abdominal conditions. The median (i.q.r.) Acute Physiology And Chronic Health Evaluation (APACHE) II score was 26 (20–32). Median IAP was 23 (21–27) mmHg before decompressive laparotomy, decreasing to 12 (9–15), 13 (8–17), 12 (9–15) and 12 (9–14) mmHg after 2, 6, 24 and 72 h. Decompressive laparotomy significantly improved oxygenation and urinary output. Survivors showed improvement in organ function scores, but non‐survivors did not. Fourteen complications related to the procedure developed in eight of the 33 patients. The abdomen could be closed primarily in 18 patients. The overall 28‐day mortality rate was 36 per cent (12 of 33), which increased to 55 per cent (18 patients) at 1 year. Non‐survivors were no different from survivors, except that they tended to be older and on mechanical ventilation. Conclusion: Decompressive laparotomy reduced IAP and had an immediate effect on organ function. It should be considered in patients with abdominal compartment syndrome. Abstract : Improves organ function